2013
DOI: 10.1111/ppl.12107
|View full text |Cite
|
Sign up to set email alerts
|

Sunflower (Helianthus annuus) long‐chain acyl‐coenzyme A synthetases expressed at high levels in developing seeds

Abstract: Long chain fatty acid synthetases (LACSs) activate the fatty acid chains produced by plastidial de novo biosynthesis to generate acyl-CoA derivatives, important intermediates in lipid metabolism. Oilseeds, like sunflower, accumulate high levels of triacylglycerols (TAGs) in their seeds to nourish the embryo during germination. This requires that sunflower seed endosperm supports very active glycerolipid synthesis during development. Sunflower seed plastids produce large amounts of fatty acids, which must be ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 47 publications
1
31
1
Order By: Relevance
“…To date, only LACS1, LACS2 and LACS8 have been localized to the ER (Zhao et al ., ; Pulsifer et al ., ), the sub‐cellular compartment of wax biosynthesis. However, a sunflower LACS8 homolog showed substrate specificity towards 16:0 and 18:2 fatty acids, suggesting a role in oil seed or phospholipid rather than wax biosynthesis (Aznar‐Moreno et al ., ). Overall, previous evidence therefore suggested that LACS1 and LACS2 are both involved in wax formation, possibly together with other homologs such as LACS4 (and LACS3).…”
Section: Discussionmentioning
confidence: 97%
“…To date, only LACS1, LACS2 and LACS8 have been localized to the ER (Zhao et al ., ; Pulsifer et al ., ), the sub‐cellular compartment of wax biosynthesis. However, a sunflower LACS8 homolog showed substrate specificity towards 16:0 and 18:2 fatty acids, suggesting a role in oil seed or phospholipid rather than wax biosynthesis (Aznar‐Moreno et al ., ). Overall, previous evidence therefore suggested that LACS1 and LACS2 are both involved in wax formation, possibly together with other homologs such as LACS4 (and LACS3).…”
Section: Discussionmentioning
confidence: 97%
“…High TAG accumulation in sunflower seed is a function of a high rate of fatty acid synthesis. This high rate of fatty acid synthesis is dependent on high efficiency of photosynthates translocation and, more importantly, high rates of key enzymes such as fatty acid synthtase, thioesterase and acyl‐CoA synthtase . Two HaLACS genes (HaLACS1 and HaLACS2) were found to be actively involved in sunflower for activation of acyl which results in the high rate of TAG accumulation in seed …”
Section: Biosynthesis Of Fatty Acids and Triglyceridesmentioning
confidence: 99%
“…In seeds, de novo fatty acid biosynthesis takes place in the plastids and it is catalyzed by the fatty acid synthase complex (FAS), producing palmitoyl-ACP (16:0-ACP) and stearoyl-ACP (18:0-ACP) as the final products (Pidkowitc et al, 2007), both of which can be desaturated by the soluble Δ 9 stearoyl-ACP desaturase to yield palmitoyl-ACP (16:1 Δ9 -ACP) and oleoyl-ACP (18:1 Δ9 -ACP: Shanklin and Cahoon, 1998;Rodríguez-Rodríguez et al, 2015). This pool of acyl-ACPs are hydrolysed by acyl-ACP thioesterases (Voelker et al, 1997;Rodríguez-Rodríguez et al, 2014), and the resulting free fatty acids are exported out of the plastid and esterified with coenzyme A by long-acyl-CoAsynthetases (Aznar-Moreno et al, 2014). These acyl-CoAs can be incorporated into phosphatidylcholine, and oleic acid can be further desaturated by endoplasmic reticulum desaturases to linoleic and linolenic acids (Kang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%